Development cooperation projects - on the road towards social organisational capital : case study: Latvia - Dutka, Sintija (2010)
DEVELOPMENT COOPERATION PROJECTS – ON THE ROAD TOWARDS SOCIAL ORGANISATIONAL CAPITAL CASE STUDY: LATVIA